An evaluation of South Korean sport psychology consultant effectiveness and its job performance between employees of athlete’s firms - Yi Liu; Jaehoon Song , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The purpose of this research is to evaluate the South Korean sport psychology consultant and its effect on job performance of all employees related to the athletes’ firms. This research study is based on primary data analysis which measures the sport psychology consultant effect on job performance. To data collection, the study uses specific questions related to sports psychology and job performance of athletes’ firms. For further analysis for the data, the author uses smart PLS software wherein the summary effect among the factors is calculated using regression analysis. Based on extracted correlation coefficients and normalised regression coefficients, the study examines 85 effect sizes in 100 plus samples selected from studies of sports organisation staff and members. Both, South Korean sport psychology and effectiveness are used as independent variables. The job performance of employees of athletes’ firm is the dependent variable of the study. Results found that South Korean sport psychology shows inverse relation between job performances of athletes’ firms. The effectiveness shows a positive effect on the job performance of employees.